2003
DOI: 10.1029/2002rs002613
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of apparent radar reflectivity due to convective clouds at attenuating wavelengths

Abstract: [1] Spaceborne precipitation radars are usually designed to operate at attenuating wavelengths, mostly at X, Ku and Ka band. At these frequencies and above, convective rainfall can cause severe attenuation. Moreover, raindrops and precipitating ice can give rise to appreciable multiple scattered radiation which apparently tends to enhance the nominal attenuated reflectivity. In order to properly describe radar observations in such conditions, apparent reflectivity has to be modeled taking into account both pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 37 publications
0
49
0
Order By: Relevance
“…Processing chain has been focused on some systematic errors that include biases and range-dependent effects, as ground clutter residuals, backscatter from sea surface, beam blocking by surrounding topography and beam attenuation along the path (Capozzi et al, 2014). The latter could be important in heavy rain or hail at X-band (Marzano et al, 2003). 5…”
Section: Radar Datamentioning
confidence: 99%
“…Processing chain has been focused on some systematic errors that include biases and range-dependent effects, as ground clutter residuals, backscatter from sea surface, beam blocking by surrounding topography and beam attenuation along the path (Capozzi et al, 2014). The latter could be important in heavy rain or hail at X-band (Marzano et al, 2003). 5…”
Section: Radar Datamentioning
confidence: 99%
“…it can take into account multiple scattering effects to any order of scattering, being the apparent radar reflectivity related to specific intensity solution of the radiative transfer equation (Marzano et al, 2000(Marzano et al, , 2003; 2. it includes, as a particular case, the modified radar equation if the apparent reflectivity factor is expressed in terms of the equivalent reflectivity factor Z e and the binaveraged extinction factor f b , i.e. :…”
Section: Generalised Radar Equation At Attenuating Wavelengthmentioning
confidence: 99%
“…In order to do this, the backscattered specific intensity, incident on the radar antenna, can be expressed by means of the apparent radar reflectivity of the considered range bin (Marzano et al, 2000;Marzano et al, 2003).…”
Section: Weather Radar Equation Within Radiative Transfer Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies at lower frequencies (Marzano et al, 2003;Battaglia et al, 2005;Kobayashi et al, 2005) have shown that multiple scattering (MS) effects become relevant in space-borne configuration at 35 GHz at high scattering optical thickness (defined as the columnar integral of the scattering coefficient), e.g. associated with large amounts of highdensity ice particles.…”
Section: Introductionmentioning
confidence: 99%